Second Newsletter of the CGIAR Initiative on Agroecology [February 2023] - Staiger Rivas, Simone; Wiederkehr Guerra, Gabriela Patricia; Quintero, Marcela; Dickens, Chris (2023)
With this newsletter, the CGIAR Initiative on Agroecology reflects on 2022 progress with the implementation of the Initiative, forming partnerships and characterizing the territories where agroecological innovations will be assessed and codesigned within particular social, economic and political contexts. With partners we are starting identifying the most suitable agroecological innovations and transition pathways.